Editorial - Khanna, Shivi (Ushus Journal of Business Management, 2016)
This issue of Ushus—Journal of Business Management brings to you four academically stimulating articles: Sudipta Kumar Jana studies the measure of e-COD payment convenience scale, its validity and reliability and how it affectscustomer loyalty. Research methods like confirmatory factor analysis and structural equation modeling have been applied with the help of SPSS and AMOS.Milind Gawai attempts to chronicle the significant milestones in the development of the concept of ‘Emotional Intelligence,’ tracing its origin from the pioneers to the present time.Dr K Venkata Janardhan Rao and Srivalli Jandhyala article is a study focused on how different food retail stores in Hyderabad metro city manage shopper perception. To analyse the perception level, GAP analysis technique is used.Roy Mathew and Dr S John Manohar study the major factors which influence the teachers to remain in any management institution. The data was collected from 261 teachers from unaided educational institutions in Bengaluru by using a structured questionnaire. Statistical tools used are factor analysis, simple averages, ANOVA and regression. The major factors affecting retention of teachers in management institutions in Bengaluru are Work Environment, Effective Leadership and Empowerment. It was also found that these factors make significant impact on the satisfaction of teachers.We wish you fruitful reading and look forward to a creative and critical feedback from our readers